2021
DOI: 10.3390/ijerph182413153
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Socioeconomic Indicators and Motor Performance of Schoolchildren in Slovakia

Abstract: Physical inactivity is currently a significant problem in Western societies. Among the many factors that affect the amount of physical activity in children, socioeconomic status, the type of school, and the area where they live can play a major role in physical development. A total of 31,620 children (6.3 ± 0.53 years; 15,726 boys; 15,893 girls), representing 55.6 % of the entire Slovak population of first graders, participated in eight motor performance (MP) tests, the results of which were correlated with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…The negative correlations between income and perceived socio-economic status and the scores on the ASQ-3 do not conform to predictions based on previous research (Ozal et al, 2020;Peric et al, 2021;Syrengelas et al, 2014). Environmental influences, such as SES, have been shown to influence infants' early neurodevelopment.…”
Section: Ses and Developmentcontrasting
confidence: 70%
See 4 more Smart Citations
“…The negative correlations between income and perceived socio-economic status and the scores on the ASQ-3 do not conform to predictions based on previous research (Ozal et al, 2020;Peric et al, 2021;Syrengelas et al, 2014). Environmental influences, such as SES, have been shown to influence infants' early neurodevelopment.…”
Section: Ses and Developmentcontrasting
confidence: 70%
“…The authors attribute this finding to the cost of engaging in specific physical activities, including the cost of equipment, transportation, and training camps. Children with families who have access to more modes of physical activity and who encourage movement tend to demonstrate more advanced motor performance (Peric et al, 2021). Due to the homogeneous sample in the current study and the age at which parents/caregivers completed the ASQ-3 for their children, the pervasive differences identified by Peric et al (2021) were unlikely to be observed.…”
Section: Ses and Developmentmentioning
confidence: 86%
See 3 more Smart Citations